Anda di halaman 1dari 5

Copyiight Ren Baiiientos Page 1

THE INVERSE LAPLACE TRANSFORM:


PARTIAL FRACTIONS AND THE FIRST SHIFTING THEOREM
As long as F(s) is relatively simple, finding its inverse transform is a matter of looking up entries on a
table of transforms, with possibly some minor modifications. However, more often than not F(s) is not a
simple expression. For example, in connection with resonant systems, we are required to find inverse
transforms of the form
L
-1
_
1
(s
2
+ k
2
)
2
_
which require either a more extensive table or some other, yet unknown property, of the transform.
One of the standard tricks, and usually our first line of attack, used in the computation of inverse
transforms is partial fraction decomposition. Review this topic before proceeding if necessary; any
standard pre-calculus algebra textbook will have an explanation of this topic.
Example 1 Find L
-1
]
s
s
2
-8s+15

Solution
1us
s
2
- 8s + 1S
=
1us
(s - S)(s -S)
=
A
s - S
+
B
s - S

A and B may be found from the identity
A(s - S) + B(s -S) = 1us; foi all s
which gives us A = -1S and B = 2S. Thus,
1us
s
2
- 8s +1S
=
-1S
s - S
+
2S
s - S

We may immediately find the inverse transform by looking up at the inverse transforms of the two terms
on the right side of the last equation:
L
-1
_
1us
s
2
-8s + 1S
_ = 2S L
-1
_
1
s - S
_ -1S L
-1
_
1
s - S
_
= 25e
5t
- 15e
3t

Example 2 Find L
-1
]
1
s
3
+s
2

Solution
1
s
3
+s
2
=
1
s
2
(s +1)
=
A
s
+
B
s
2
+
C
s +1

A, B andC may be found from the equation
As(s + 1) + B(s + 1) + Cs
2
= 1
Solving this identity for its coefficients gives us A = -1, B = 1, C = 1. Thus
1
s
3
+s
2
=
-1
s
+
1
s
2
+
1
s +1

Once again, we just need to look up the corresponding entries on a table:
L
-1
_
1
s
3
+s
2
_ = L
-1
_
1
s
2
_ + L
-1
_
1
s +1
_ - L
-1
_
1
s
_
= t + e
-t
- 1
Example 3 Find L
-1
]
2s
2
-s+2
s
3
-s
2
+2s-2


Copyiight Ren Baiiientos Page 2

Solution
2s
2
- s + 2
s
3
-s
2
+2s - 2
=
2s
2
- s + 2
s
2
(s -1) +2(s - 1)
=
2s
2
- s + 2
(s
2
+2)(s -1)

Thus,
2s
2
- s + 2
(s
2
+2)(s - 1)
=
As + B
s
2
+2
+
C
s -1

We find A, B, and Cby identifying coefficients of the identity
(As +B)(s - 1) + C(s
2
+2) = 2s
2
-s +2
Solving for A, B, and C
2s
2
-s +2
s
3
-s
2
+2s -2
=
s
s
2
+ 2
+
1
s - 1




We are ready to find the inverse transform.
L
-1
_
2s
2
- s + 2
s
3
-s
2
+2s - 2
_ = L
-1
_
s
s
2
+ (2)
2
_ + L
-1
_
1
s - 1
_
= us(2t) +e
t

Example 4 Find L
-1
]
2s
2
s
4
+13s
2
+36

Solution
2s
2
s
4
+ 1Ss
2
+S6
=
As + B
s
2
+4
+
Cs +
s
2
+9

We determine the constant A, B, C, and D by identifying coefficients of the identity
(As + B)(s
2
+ 9) + (Cs +)(s
2
+ 4) = 2s
2

That is
As
3
+ Bs
2
+ 9As +9B + Cs
3
+ s
2
+4Cs + 4 = 2s
2

Identifying coefficients:
A + C = u (cubic tcrms)
B + = 2 (quoJrotic tcrms)
9A +4C = u (lincor tcrms)
9B +4 = u (constont tcrms)
Solving this system: A = C = u, B = -8S, = 18S.
Thus,
L
-1
_
2s
2
s
4
+1Ss
2
+ S6
_ = L
-1
_
-8S
s
2
+4
+
18S
s
2
+9
_
= -
8
1u
L
-1
_
2
s
2
+4
_ +
18
1S
L
-1
_
S
s
2
+9
_
= -
4
5
stn2t +

5
stn3t
The Inverse Transform and the First Shifting Theorem
The First Shifting Theorem allows us to find inverse transforms when we cannot use partial fractions.
For example the denominator of
us kt, k = 2 e
at
, a = 1 These are associated with
Copyiight Ren Baiiientos Page S

F(s) =
4
s
2
- 6s + 2S

cannot be factored. How then do we find L
-1
{F(s)]? The best that we can do is complete squares
4
s
2
- 6s +2S
=
4
(s - S)
2
+16

but still this takes us nowhere. It is the First Shifting Theorem that will help us to find this inverse
transform. It states:


which is of course a consequence of the result previously derived:
L{e
at
(t)] = F(x - a)
A more practical way of writing the result in the box is this: once you recognize the shifted function, compute
the inverse transform of the un-shifted function and multiply the result by c
ut
:
L
-1
{F(x - a)] = e
at
L
-1
{F(x)]
or
L
-1
{F(x)|
x-a
] = e
at
L
-1
{F(x)] = L
-1
{F(x)] e
at

Where the factor e
at
is placed is a matter of preference.
Let us revisit the problem of finding
L
-1
_
4
s
2
-6s + 2S
_ = L
-1
_
4
(s -S)
2
+ 16
_
The expression on the right-hand side of this equation looks like
L
-1
{F(x)|
x-a
]
with F(x) =
4
s
2
+16
and a = 3, that is,
L
-1
_
4
(s -S)
2
+ 16
_ = L
-1
__
4
s
2
+16
]_
x-3
_
Thus,
L
-1
_
4
(s - S)
2
+16
_ = c
3t
L
-1
_
4
s
2
+16
_
= e
3t
(stn4t)
Example 5 Find L
-1
]
1
(s+5)
3

Solution
Let F(s) =
1
s
S
, then
1
(s+5)
3
= F(s +S) = F(s -(-S)). Thus,
L
-1
_
1
(s + S)
3
_ = L
-1
|F(s -(-S))|
= L
-1
{F(s)] c
-5t

= c
-5t
L
-1
_
1
s
5
_
=
c
-5t
4!
L
-1
_
4!
s
5
_
=
c
-5t
4!
t
4

L
-1
{F(x - a)] = e
at
(t)
Copyiight Ren Baiiientos Page 4

Thus,
L
-1
_
1
(s + S)
3
_ =
c
-5t
4!
t
4

Example 6 Compute

L
-1
]
s
s
2
-6s-7

Solution
Complete squares:
s
s
2
- 6s -7
=
s
s
2
- 6s + 9 - 9 - 7

=
s
(s -S)
2
- 16

Now we must make sure that this is a shifted F(s). Notice that the denominator has s - S.
However, the numerator does not. We can fix this by adding and subtracting S: s = s -S +S.
Thus,
s
(s - S)
2
-16
=
s - S +S
(s -S)
2
- 16

=
s -S
(s -S)
2
- 16
-
S
(s -S)
2
- 16

=
s -S
(s -S)
2
- 16
-
S
4
4
(s -S)
2
- 16

=
s
s
2
-4
2

s-3
-
S
4

4
s
2
- 4
2
_
s-3

Thus,
L
-1
_
4
s
2
- 6s -6
_ = L
-1
_
s
s
2
- 4
2

s-3
_ -
S
4
L
-1
_
4
s
2
- 4
2
_
s-3
_
= c
3t
cosh(4t) -c
3t
S
4
sinh(4t)
= e
3t
_ush(4t) -
3
4
stnh(4t)_
Exercise: This example can also be done using partial fractions. Show that the result is the same.

Example 6 (a monster) Find L
-1
]
2s
3
-s
2
(4s
2
-4s+5)
2

Solution
First, notice that we are justified in using partial fractions since the numerator is of lesser degree
than the denominator. Thus,
2s
3
- s
2
(4s
2
-4s + S)
2
=
2s
3
-s
2
(4s - S)
2
(s +1)
2
=
A
4s -S
+
B
(4s - S)
2
+
C
s +1
+

(s +1)
2

We find A, B, C, and D by identifying the coefficients of the identity
A(4s -S)(s + 1)
2
+B(s +1)
2
+ C(s + 1)(4s - S)
2
+(4s - S)
2
= 2s
3
- s
2

Expanding the left-hand side:
A(4s
3
+ Ss
2
- 6s -S) +B(s
2
+2s + 1) + C(16s
3
- 24s
2
-1Ss + 2S)
+(16s
2
- 4us +2S) = 2s
3
-s
2

Equating coefficients:
4A + 16C = 2
SA +B - 24C + 16 = -1
Copyiight Ren Baiiientos Page S

-6A +2B - 1SC - 4u = u
-SA + B + 2SC + 2S = u
This system may be solved by a number of methods. We relied on Mathematica to assist us with
the computation and here is the syntax:
In[1]: M={{4,0,16,0},{3,1,-24,16},{-6,2,-15,-40},{-5,1,25,25}}
Out[1]: {{4, , 1, ], {3, 1, -24, 1], {-, 2, -15, -4], {-5, 1, 25, 25]]
In[2]: M. {a, h, c, d] == {2, -1, , ]
Out[2]: {4a + 1c, 3a + h -24c + 1d, -a + 2h -15c - 4d, -5a + h + 25c +
25d] == {2, -1, , ]
In[3]: Sulve|%, {a, b, , d]]
Out[3]: {{a -
115
48
, h -
25
54
, c -
1
243
, d - -
1
27
]]
Thus, A = 11S486, B = 2SS4, C = 1624S, = -127 and
2s
3
-s
2
(4s
2
- 4s +S)
2
=
11S486
4s -S
+
2SS4
(4s - S)
2
+
1624S
s + 1
-
127
(s + 1)
2

=
11S
1944

1
s - S4
+
2S
864

1
(s - S4)
2
+
16
24S

1
s -(-1)
-
1
27

1
(s -(-1))
2

We may now proceed to find the inverse transform:
L
-1
_
2s
3
-s
2
(4s
2
-4s +S)
2
_ =
11S
1944
L
-1
_
1
s - S4
_ +
2S
864
L
-1
_
1
(s - S4)
2
_ +
16
24S
L
-1
_
1
s - (-1)
_
-
1
27
L
-1
_
1
(s - (-1))
2
_
=
115
1944
e
5t4
+
25
84
t e
5t4
+
1
243
e
-t
-
1
27
t e
-t

Notice that we used the First Shifting Theorem in the second and last terms:
L
-1
n!
(s - o)
n+1
= t
n
c
ut

The Mathematica syntax for this computation is as follows:
In[4]: InverseLaplaceTransform[(2s^3-s^2)/(4s^2-4s+5)^2,s,t]
Out[4]: {{a 115/486, b 25/54, c 16/243, d -(1/27)}}
Out [5]:
1
128
c
(
1
2
-1)t
((8 + 41) +(8 -41)c
21t
+(4 -S1)t + (4 + S1)c
21t
t)
The symbol 1 is used in Mathematica to denote the complex number -1 . Mathematica uses a different
procedure to compute inverse transforms and therefore its answers will usually involve the more
economical notation of complex variables.